Correlation study and significance of the EGFR expression in serum, lymph nodes and tumor tissue of NSCLC. Issue 1 (January 2014) - Zhuo, Yinling; Guo, Qisen; Song, Pingping; Zhang, Qiong; Guo, Chen; Zeng, Hongsheng; Guan, Yan; Liu, Xiuju; Zhao, Chenqing
Abstract Background This study was designed to detect the protein expression of epidermal growth factor receptor (EGFR) among serum, lymph node, and tumor tissues, and to discuss their relationship and clinical significance. We investigated whether EGFR levels in serum and lymph nodes could be used as an effective method for non‐small cell lung cancer (NSCLC) to diagnose and assess clinical stage. Methods In 56 patients with NSCLC and 10 individuals with nonmalignant thoracic disease, we measured EGFR levels in serum using an enzyme immunoassay, and EGFR mRNA levels in lymph node and NSCLC tissues by quantitative real‐time‐polymerase chain reaction. We examined the correlation between them and with the clinical parameters. Results Serum EGFR levels substantially decreased after surgical treatment (P < 0.001). Serum EGFR levels were correlated with smoking, surgery, and pathological type after surgery (all P < 0.05). EGFR mRNA levels in lymph node and tumor tissues were correlated more closely with lymph node metastasis (P = 0.015. EGFR mRNA in tissues was higher than that of benign pulmonary diseases (P = 0.020). There was an obvious positive correlation among EGFR levels of serum and lymph node tissues (r = 0.764; P < 0.001), serum and tumor tissues (r = 0.616; P < 0.001), and lymph node and tumor tissues (r = 0.904; P < 0.001) in NSCLCs. Conclusion The data suggest that detecting EGFR levels in serum and lymph node tissues could be a simple and effective method to diagnose and assess the clinical stage in patients with NSCLC.